Algoritma RSA (Rivest–Shamir–Adleman) pada Sistem Informasi Pemilihan Ketua Organisasi Ikatan Pondok Pesantren Smart-SIPKOTREN - Hasbulloh, Hasbulloh; Fitri, Iskandar; Ningsih, Sari (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The objectives of this research are; 1) Help simplify the process of selecting the chairman who previously used the manual method or did not have a web-based evaluation application, 2) This application can secure the details of the names that have chosen the chairman through the admin, only the admin knows, and 3) Improve speed and accuracy the results of the e-voting data that replaced the previous conventional voting system were carried out manually. In making the application, implementing RSA (Rivest–Shamir–Adleman) on the e-voting system that was built, for designing the application using web-based programming languages such as HTML, PHP, and MySQL used as e-voting database management. The results showed that the e-voting application simplifies the vote-counting process because it is done online and you can find out directly the results of the upcoming elections, without the need to count votes like a manual selection process. the participation of students in Islamic boarding schools is determined as the maximum power. The election of the head of the hut has become an inseparable part of the hut, almost all the huts hold elections. The election of the chairman is the procedure for selecting the representative of the booth in the booth based on the majority of votes.